Patterns and Determinants of Imported Malaria near the Argentina–Bolivia Border, 1977–2009 - Erica Berlin; Roberto D. Coello-Peralta; Pedro Cedeño-Reyes; Elsa M. Valle-Mieles; Paul L. Duque; Mario O. Zaidenberg; Horacio Madariaga; Juan C. Navarro; María J. Dantur-Juri; Marcia C. Castro (Pathogens, 2025)
In the Americas, the number of confirmed malaria cases decreased by 65.4% between 2000 and 2023, and malaria elimination is now in sight for many countries. Argentina is currently free of autochthonous malaria transmission. Until 2011, cases of malaria were concentrated in Northwestern Argentina, near the border with Bolivia, a country that continues to have malaria transmission. The Orán department (Salta province, Northwestern Argentina) had particularly high transmission near a main road that is a pathway for migration from Bolivia. The purpose of this study was to identify which factors best explain the extent and timing of changes in the proportion of malaria cases in this area that were locally transmitted versus acquired in another country. Combining information from routinely collected case investigations, epidemiological surveillance data, and satellite imagery, we used a logistic model and a multi-level model of change to identify how demographic and place-level variables influence the proportion of malaria cases that were imported over time. The findings showed that the proportion of cases that were imported varied significantly over time, with a clear trend from predominantly autochthonous cases at the beginning of the study in 1977 (94.52%) to a majority of imported cases in 1992 (53.33%), a pattern that continued and intensified, reaching 76% imported cases by the end of the series in 2009. Nationality and place of work were key demographic factors influencing this shift. In particular, there was a change in transmission patterns after a cross-border intervention was launched in 1996. As Argentina has obtained certification of malaria elimination, these results may inform focal strategies for preventing re-introduction.